2022
DOI: 10.3389/fmicb.2022.965292
|View full text |Cite
|
Sign up to set email alerts
|

Healthy Gut Microbiome Composition Enhances Disease Resistance and Fat Deposition in Tibetan Pigs

Abstract: The gut microbiota is involved in a range of physiological processes in animals, and modulating the microbiome composition is considered a novel target for identifying animal traits. Tibetan pigs show better fat deposition and disease resistance compared to Yorkshire pigs. However, studies investigating the correlation between favorable characteristics in Tibetan pigs and the gut microbial community remain scarce. In the current study, 1,249,822 high-quality sequences were obtained by amplicon sequencing of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 65 publications
(67 reference statements)
2
5
0
Order By: Relevance
“…Tibetan pigs are an indigenous fatty pig breed in high-altitude and cold areas of China and are raised mainly through stabling and half-stabling feeding with a fiber-rich diet [ 39 ]. A study of the gut microbiome in Tibetan pigs indicated that Bifidobacteria, Ruminococcaceae, and Family-XIII-AD3011-Group were conducive to improving disease resistance in Tibetan pigs, and Lactobacillus and Solobacterium were observed to be the main bacterial communities involved in fat deposition in Tibetan pigs [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Tibetan pigs are an indigenous fatty pig breed in high-altitude and cold areas of China and are raised mainly through stabling and half-stabling feeding with a fiber-rich diet [ 39 ]. A study of the gut microbiome in Tibetan pigs indicated that Bifidobacteria, Ruminococcaceae, and Family-XIII-AD3011-Group were conducive to improving disease resistance in Tibetan pigs, and Lactobacillus and Solobacterium were observed to be the main bacterial communities involved in fat deposition in Tibetan pigs [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…In cecal and colonic contents of rats, negative correlations between the Family XIII AD3011 group and acetic acid ( Shi et al, 2020 ). In another study, the Family XIII AD3011 group was conducive to improving disease resistance in Tibetan pigs ( Shang et al, 2022 ). Pediococcus has been shown to be effective in the production of antimicrobial peptides with applications in the food and health industries ( Todorov et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…The composition of the gut microbiota is significantly influenced by dietary factors. Through its intricate interactions with the host, the gut microbiota exerts a profound influence on various aspects of host physiology, including the maintenance of homeostasis, organ development, metabolic processes, and immune response ( Fouhse et al, 2016 ; Shang et al, 2022 ). According to the PCoA result, the two groups were clearly separated, suggesting significant influences in bacterial composition among the L-Cit group.…”
Section: Discussionmentioning
confidence: 99%